The examination of the attitude of the science subject in view of a pilot study (Training and Practice : Journal of Educational Sciences, 2019)
This research examines the effectiveness of science education in KS1-2 (lower primary) in a variety of environments and with different methods. Our research also includes the mapping of the emotional attitude and learning habits of 3d grade pupils related to the science school subject, as well as the attitude and teaching methods of educators teaching the subject. This study is to present the results of the tests of pupils’ emotional and cognitive components. The research has been implemented at Kaposvár University with the support of Programme P4/1 “Methodological research and development in support of child development, public education and higher education - a healthy society and a healthy environment” in the framework of EFOP-3.6.1-16-2016-00007 project “Smart specialization programme at Kaposvár University”.